2014
DOI: 10.1177/1938640014548419
|View full text |Cite
|
Sign up to set email alerts
|

Medial Malleolar Osteotomy and Osteochondral Autograft Transfer for Osteochondritis Dissecans of the Distal Tibial Plafond

Abstract: Therapeutic, Level IV: Case report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…26 Although not widely used during arthroscopic treatment of OLTPs, other studies have shown that additional accessibility can be achieved with the use of arthrotomies and malleolar osteotomies. 19,33 Although our data suggest that ankle distraction is necessary for adequate arthroscopic accessibility of the distal tibial plafond, distraction is not without complications. Ankle distraction significantly increases capsular tension and reduces the safe zone between the anterior distal tibial plafond and anterior neurovascular structures during arthroscopy.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…26 Although not widely used during arthroscopic treatment of OLTPs, other studies have shown that additional accessibility can be achieved with the use of arthrotomies and malleolar osteotomies. 19,33 Although our data suggest that ankle distraction is necessary for adequate arthroscopic accessibility of the distal tibial plafond, distraction is not without complications. Ankle distraction significantly increases capsular tension and reduces the safe zone between the anterior distal tibial plafond and anterior neurovascular structures during arthroscopy.…”
Section: Discussionmentioning
confidence: 70%
“…26 Although not widely used during arthroscopic treatment of OLTPs, other studies have shown that additional accessibility can be achieved with the use of arthrotomies and malleolar osteotomies. 19,33…”
Section: Discussionmentioning
confidence: 99%
“…The donor areas of autologous osteochondral bone graft are restricted; therefore, for major defects, the allograft represents an option for the tibiotarsal joint with large osteochondral lesions of the talus (10) . Few articles describe this technique for tibial defects (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Most osteochondral defects of the tibial plafond are post-traumatic [5] , [6] , [7] , [9] , [11] , [13] , [18] . Such a post-traumatic lesion is an antecedent factor for the development of degenerative changes in several reports [3] , [13] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…OAT in the knee joint is well established and has good results for the treatment of osteochondral defects, and the results of treatment of talar dome lesions have suggested that OAT has good long-term clinical outcomes [8] . However, only a few cases of using OAT for osteochondral defects of the tibial plafond have been reported in the literature [18] . This case report provides an important clinical insight.…”
Section: Discussionmentioning
confidence: 99%